Team-Based Intervention to Reduce the Impact of Nonactionable Alarms in an Adult Intensive Care Unit. Issue 2 (April 2020) - Yeh, Justin; Wilson, Ruth; Young, Lufei; Pahl, Lisa; Whitney, Steven; Dellsperger, Kevin C.; Schafer, Pascha E.
Abstract : Background: Nonactionable alarms comprise over 70% of alarms and contribute a threat to patient safety. Few studies have reported approaches to translate and sustain these interventions in clinical settings. Purpose: This study tested whether an interprofessional team-based approach can translate and implement effective alarm reduction interventions in the adult intensive care unit. Methods: The study was a prospective, cohort, pre- and postdesign with repeated measures at baseline (preintervention) and post-phase I and II intervention periods. The settings for the most prevalent nonactionable arrhythmia and bedside parameter alarms were adjusted during phases I and II, respectively. Results: The number of total alarms was reduced by 40% over a 14-day period after both intervention phases were implemented. The most prevalent nonactionable parameter alarms decreased by 47% and arrhythmia alarms decreased by 46%. Conclusions: It is feasible to translate and sustain system-level alarm management interventions addressing alarm fatigue using an interprofessional team-based approach. Abstract : Supplemental Digital Content is Available in the Text.